Shock-induced radiation belt dynamics: simultaneous observations of “one-kick” acceleration and ultralow frequency modulation - Chen, Xingran; Lu, Xi; Zong, Qiugang; Zhang, Hui; Liu, Ying; Zhou, Xuzhi (Frontiers in Astronomy and Space Sciences, 2024)
We present conjunctive observations to study the prompt responses of radiation belt electrons during the interplanetary shock (IPS) event on 7 September 2017. As the IPS impinged the Earth, the Time History of Events and Macroscale Interactions (THEMIS) E spacecraft located near the dayside bow shock observed alternating features of solar wind and magnetosheath, indicating that the magnetosphere was repeatedly compressed. Following each compression, rapid increases of relativistic electron fluxes and the corresponding drift echoes were well identified over the energy and pitch-angle spectra obtained by the Van Allen Probes (RBSP) in the inner magnetosphere. Meanwhile, oscillations in the Pc4 range are embedded in the flux variations, appearing as straight stripes in the pitch-angle distributions observed by RBSP-B inside the wave active region and “boomerang” stripes in the observations obtained by RBSP-A ∼6 MLT away. Such diverse signatures suggested an azimuthally confined ultralow frequency (ULF) wave. The patterns in the observed particle spectra agreed well with the theoretical predictions, by which we conclude that the surfing acceleration by the shock-induced pulse and the continuous modulation by the localized ULF wave conspired to cause significant disturbances to the Earth’s radiation belt.